The Influence of Intrinsic and Extrinsic Factors on the Participation of Women in Fertile Age Couples (PUS) in the Asamasetat Visualization (IVA) Inspection Program at the Sigalingging Health Center, Parbuluan District, Dairi Regency in 2015 - Rugun Togianur Lingga; Risdiana Melinda Naibaho (Institute of Computer Science (IOCS), 2020)
The latest survey about cervical cancer showed 40,000 new cases of cervical cancer in Southeast Asia, and 22,000 of them died. In Indonesia, an estimated 15,000 new cases of cervical cancer occur each year, while the death rate estimated 7500 cases per year. This research is a research method analytic survey with cross sectional design (cross-sectional) to determine the intrinsic factor (knowledge, attitude), extrinsic factors (husband's support, exposure information), while the dependent variable (Y) is the participation of women in the examination IVA in PHC Sigalingging. The population in this study were women EFA in Puskesmas Sigalingging, as many as 2,327 people. Samples were taken randomly with the inclusion criteria were women of EFA and sexually active, aged 15- 45 years as many as 122 people. The results showed no influence between knowledge and participation of women of child bearing age in the examination methods of IVA with a p-value = 0.011 <0.05. There is influence between attitudes to the participation of women of childbearing age in the examination methods of IVA with a p-value = 0.008> 0.05. There is no effect between the support of husband / family with the participation of women of childbearing age with a p-value = 0.062> 0.05. No effect between exposure to the participation of women of childbearing age with a p-value = 0.013 <0.05. Suggestion: For PHC Sigalingging in order to improve health education activities on early detection of cervical cancer methods IVA, and for DHO Dairi: in order to give a fillip to the health center pilot IVA and add the number of trained personnel IVA,